Normative Differences Between the 2020 Supreme Court’s Landmark Decision and SEMA Number 3 of 2018 Regarding Polygamy Isbat - Hartini Hartini; Faiz Rahman; Dita Elvia Kusuma Putri; Ahmad Bunyan Wahib; Yulkarnain Harahab (Universitas Negeri Semarang, 2026)
This study aims to (a) analyse the position of Landmark Decision in the current Indonesian legal system, (b) examine and analyse the contradiction between SEMA Number 3 of 2018 and 2020 Landmark Decision or religious civil law decision Number 223K/Ag/2020, and (c) explore ideal solutions for the case of validating unregistered polygamous marriages when there are different legal principles between SEMA Number 3 of 2018 and 2020 Landmark Decision. This research is normative legal research using secondary data obtained through a literature study as well as statute approach, case approach, and conceptual approach. The results show that (a) theoretically, landmark decisions are stronger than jurisprudence because they have significant values that change the textual meaning of positive law and contain legal rules that will have implications for the development of law in Indonesia compared to the power of jurisprudence. (b) The contradiction between SEMA Number 03 of 2018 and the 2020 Landmark Decision occurs because SEMA establishes legal norms that completely isolate efforts to validate unregistered marriages due to polygamy by targeting the core procedural law related to formal procedural requirements, with the term “not admissible” or niet ontvankelijke verklaard, while the cases brought to the court are certainly causal in nature and cannot be generalized. (c) The settlement of the cases of marriage validation due to unofficial polygamy is by adhering to SEMA Number 03 of 2018 through discretion while referring to the 2020 Landmark Decision with some strict conditions.